2014
DOI: 10.1042/bj20140923
|View full text |Cite
|
Sign up to set email alerts
|

Solution structures and dynamics of ADF/cofilins UNC-60A and UNC-60B fromCaenorhabditis elegans

Abstract: The nematode Caenorhabditis elegans has two ADF/cofilin isoforms, UNC-60A and UNC-60B, which are expressed from the unc60 gene by alternative splicing. UNC-60A has higher activity to cause net depolymerization, and to inhibit polymerization, than UNC-60B. UNC-60B, on the other hand, shows much stronger severing activity than UNC-60A. To understand the structural basis of their functional differences, we have determined the solution structures of UNC-60A and UNC-60B proteins and characterized backbone dynamics.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 47 publications
(120 reference statements)
1
4
0
Order By: Relevance
“…However, superposition of PDB entry 7rtx onto PDB entry 5yu8 shows that the -turn of actophorin is in the vicinity of the ADP-bound actin and this may be related to the observation that actophorin has a tenfold higher binding affinity for ADP-F-actin over ATP-F-actin (Blanchoin & Pollard, 1999), and is consistent with molecular-dynamics simulations and other computations of the effect of ADF/C binding to actin filaments (Pfaendtner et al, 2010;Schramm et al, 2017). In addition, NMR studies of two isoforms of cofilin from Caenorhabditis elegans, UNC-60A and UNC-60B, revealed nanosecond-to-picosecond dynamics localized to their F-loop; these dynamics were used to explain the differential activity toward actin depolymerization of these homologs in this invertebrate species (Shukla et al, 2015). The severing action of actophorin (Maciver et al, 1991) is similar to that of other members of the ADF/C family, notably cofilin (De La Cruz, 2009;Ono, 2007).…”
Section: Discussionsupporting
confidence: 80%
“…However, superposition of PDB entry 7rtx onto PDB entry 5yu8 shows that the -turn of actophorin is in the vicinity of the ADP-bound actin and this may be related to the observation that actophorin has a tenfold higher binding affinity for ADP-F-actin over ATP-F-actin (Blanchoin & Pollard, 1999), and is consistent with molecular-dynamics simulations and other computations of the effect of ADF/C binding to actin filaments (Pfaendtner et al, 2010;Schramm et al, 2017). In addition, NMR studies of two isoforms of cofilin from Caenorhabditis elegans, UNC-60A and UNC-60B, revealed nanosecond-to-picosecond dynamics localized to their F-loop; these dynamics were used to explain the differential activity toward actin depolymerization of these homologs in this invertebrate species (Shukla et al, 2015). The severing action of actophorin (Maciver et al, 1991) is similar to that of other members of the ADF/C family, notably cofilin (De La Cruz, 2009;Ono, 2007).…”
Section: Discussionsupporting
confidence: 80%
“…7 and Ref. 45). This may contribute to the observed differences in binding affinity, cooperativity, and severing activity.…”
Section: Ser-3 Modification Repositions the Cofilin N Terminus Away Fmentioning
confidence: 91%
“…The F-site locates in the N-terminus, which is responsible for binding to F-actin and severing actin filaments. The G/F-site, locates in the C-terminus, binds to both G-actin and F-actin in the same ratio (Nishida et al, 1984 ; Lappalainen et al, 1998 ; Shukla et al, 2015 ). The sequence schematic and ribbon diagrams are shown in Figure 1 .…”
Section: Structure Of Cofilinmentioning
confidence: 99%